PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Fauzan Ariel; M. Fahri Albar; Muhammad Hasan Basari (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
The principal plays a strategic role in determining the direction and success of education within the institution they lead. This article aims to describe the role of school principals in improving the quality of education through the application of educational management functions, including planning, organizing, implementing, and supervising. Historically, the leadership role of principals has evolved since the early 20th century when schools began to adopt modern management concepts inspired by industrial and organizational theories. Over time, the principal's position transformed from a mere administrator into an educational leader responsible for fostering innovation and quality learning. This study employs a descriptive qualitative approach using literature review methods to analyze educational management theories and their real implementation in schools. The findings indicate that effective principals act as visionary leaders, skilled managers, and motivators for teachers and students. By applying participatory management principles and transformational leadership, the quality of education can be continuously improved